Impact Micro influencer Credibility And Brand Authenticity Impact of Consumer Trust in MS Glow Products on TikTok - Ravli Agas Syahbani; Rahmadi Rahmadi (CV. AFDIFAL MAJU BERKAH, 2026)
This research aims to analyze The Influence of Micro Influencer Credibility and Brand Authenticity on Consumer Trust on MS Glow products on the TikTok platform. Development technology digital has change landscape marketing, make media social media as the main means of building brand communication and influencing consumer behavior. Based on Source Credibility Theory, Brand Authenticity Theory, And Consumer Trust Theory, study This test How micro credibility And Brand Authenticity can build consumer trust, which is an important factor in purchasing decision making. The method used was Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected through a questionnaire from 154 respondents. Which is users product MS Glow in TikTok. Results analysis shows that both Micro Influencer Credibility and Brand Authenticity have a significant influence on Consumer Trust. The combination of Micro influencer credibility and brand authenticity have been proven to contribute positively to building consumer trust, Which on it's his turn increase decision purchase product in platform social media. This research provides a theoretical contribution in developing an understanding of the influence of influencer credibility and brand authenticity in the context of digital marketing, as well as give implications practical for strategy marketing in platform media social, especially for the local skincare industry.